Low Skeletal Muscle Mass Impairs Quality of Life in Nasopharyngeal Carcinoma Patients Treated With Concurrent Chemoradiotherapy - Hua, Xin; Liao, Jun-Fang; Liu, Shan; Zhang, Jun; Huang, Han-Ying; Wen, Wen; Long, Zhi-Qing; Zhang, Wen-Wen; Guo, Ling; Lin, Huan-Xin (Frontiers in Nutrition, 2020)
Background: Nasopharyngeal carcinoma (NPC) patients receiving concurrent chemoradiotherapy (CCRT) frequently develop sarcopenia, but little is known about its effects on health-related quality of life (QOL). Methods: We retrospectively assessed 56 patients with locoregionally advanced NPC enrolled in a prospective trial. We determined sarcopenia on routine computed tomography (CT) simulation scans taken before radiotherapy, at the third cervical (C3) vertebral level with validated sex-specific cutoffs. QOL was assessed using the World Health Organization Quality of Life Questionnaire-100 at baseline and after 3 weeks. Pain was scored every 24 h using a numerical rating scale (NRS). Characteristics related to sarcopenia were identified by logistic regression. The chi-square test was used to examine the association of sarcopenia with QOL and pain. Results: Of the 56 participants (mean age 44.20 ± 10.93 years), over half (60.71%) developed sarcopenia. Patients with sarcopenia were more likely to be older (P = 0.035), male (P = 0.066), have a lower body-mass index (BMI; P = 0.091), and have a higher pain score (P = 0.001). Older age (hazard ratio [HR] = 1.788, P = 0.016), being male (HR = 3.145, P = 0.010), lower BMI (HR = 0.761, P = 0.033), and lower prognostic nutritional index (HR = 0.186, P = 0.034) were associated with higher risk of sarcopenia. Sarcopenia was associated with poorer baseline QOL scores (P = 0.072), especially in the physical domain (P = 0.002) and its three facets: pain (P = 0.003), energy (P = 0.021), and sleep (P = 0.007). Sarcopenia was also associated with significantly worse QOL scores (P = 0.006) at 3 weeks, especially in the physical (P = 0.002), psychological (P = 0.046), independence (P = 0.003), and social domains (P = 0.023), and in general health condition (P = 0.043). Conclusions: The incidence of sarcopenia, as evaluated using routine CT simulation scans, is high in patients receiving CCRT for locoregionally advanced NPC. Sarcopenia results in poorer QOL and higher pain scores, which underscores the requirement for nutritional and functional interventions to address sarcopenia early in the treatment course.